Dragonflight - McCaffrey, Anne (McCaffrey, Anne. Dragonriders of Pern, 1991)
On the beautiful planet Pern, colonized for centuries, Land Holders and Craftsmen have traditionally tithed food and supplies to the dragonweyrs to which they are bound. In times past, the mighty telepathic dragons and their riders were the only protection from the dreaded, life-threatening Thread. But it has been over 400 years since the last Threadfall, and some people have come to doubt that the menace will every strike again. But F'lar, rider of Pern's greatest bronze dragon, has no such illusions. The Red Star is near; Thread will fall soon.